Does Social Media Marketing Influences Consumer Purchase Decisions at Marketplace? - Febri Rakhmawati (Universitas Airlangga, 2023)
The purpose of this study was to explore the role that social media marketing plays on purchasing decision making process at Shopee marketplace. This research uses quantitative methods using SPSS with simple linear regression. Data collection was obtained by distributing questionnaires online via the Googleform link to 100 respondents. Testing in this study using hypothesis testing using the t test and f test. The results of this study indicate that social media marketing variables have no significant effect on consumer purchasing decisions at Shopee marketplace. Therefore, effective application of social media should be a part of any business' marketing strategy. For example, social media visuals, content, promotional activities, and use of opinion leader influence should be deployed to positively influence the buying behaviors of consumers. This research brings any managerial implication, especially Shopee management to take concern business marketing strategy to optimize social media marketing impacts on customer in purchasing decisions.